The Great Humanist of the Middle Ages: Grigor Narekatsi - Haroyan, Hayk; Haroyan, Nelli (Bulletin of Yerevan University E: Philosophy, Psychology, 2013)
The present article highlights the problem of humanism in G. Narekatsi’s poem entitled “The Book of Tragedy”. The peculiar features of his outlook such as antropocentrism, humanism, defense of the rights of logic are displayed here. By worshipping man as the greatest value, by preaching logical faith as the true means of cognition of God and a means of mastering human character Narekatsi proves to be a true guardian of humanism.
Keywords: .